Penerapan Media Augmented Reality dalam Meningkatkan Hasil Belajar Akidah Akhlak Materi Tasawuf Siswa Kelas XI MAN 2 Kota Kediri - Siti Nurhalizah M; Nila Lukmatus Syahidah; Cantika Sari Dewi M; Siti Maria Ulfa Mattarima (PTK: Jurnal Tindakan Kelas, 2025)
This research is motivated by the low learning outcomes of Grade XI students at MAN 2 Kota Kediri in the subject of Tasawuf, where 47,06% of students scored below the Minimum Mastery Criteria (KKM) of 78. The purpose of this study is to determine the effectiveness of Augmented Reality (AR)-based learning media in improving student learning outcomes. This research employed a Classroom Action Research (PTK) approach, carried out in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The research subjects were 34 students from Grade XI Science and Technology at MAN 2 Kota Kediri. Data collection techniques included observation, interviews, and  cognitive tests. The results showed that the average student score increased from 74.41 with 47% mastery in the pre-action phase, to 89.26 with 79.41% mastery in cycle I, and reached 99.1 with 100% mastery in cycle II. These findings demonstrate that AR-based media is effective in enhancing students' understanding of abstract material such as Tasawuf, while also increasing their engagement in the learning process.